KRAS G12C-mutated advanced non-small cell lung cancer: A real-world cohort from the German prospective, observational, nation-wide CRISP Registry (AIO-TRK-0315). (April 2021) - Sebastian, Martin; Eberhardt, Wilfried E.E.; Hoffknecht, Petra; Metzenmacher, Martin; Wehler, Thomas; Kokowski, Konrad; Alt, Jürgen; Schütte, Wolfgang; Büttner, Reinhard; Heukamp, Lukas C.; Stenzinger, Albrecht; Jänicke, Martina; et al.
Highlights: CRISP prospectively collected real-world data on advanced NSCLC and KRAS mutations. Of 1039 patients, 39.5 % had KRAS mutations, 38.9 % of these were KRAS G12C-mutated. KRAS G12C-mutated advanced NSCLC has poor outcome under current standard therapy. Valuable historical control for upcoming clinical studies on KRAS -inhibitors. Abstract: Objectives: After decades of unsuccessful efforts in inhibiting KRAS, promising clinical data targeting the mutation subtype G12C emerge. Since little is known about outcome with standard treatment of patients with G12C mutated non-small cell lung cancer (NSCLC), we analyzed a large, representative, real-world cohort from Germany. Patients and methods: A total of 1039 patients with advanced KRAS -mutant or -wildtype NSCLC without druggable alterations have been recruited in the prospective, observational registry CRISP from 12/2015 to 06/2019 by 98 centers in Germany. Details on treatment, best response, and outcome were analyzed for patients with KRAS wildtype, G12C, and non-G12C mutations. Results: Within the study population, 160 (15.4 %) patients presented with KRAS G12C, 251 (24.2 %) with non-G12C mutations, 628 (60.4 %) with KRAS wildtype. High PD-L1 expression (Tumor Proportion Score, TPS > 50 %) was documented for 28.0 %, 43.5 %, and 28.9 % (wildtype, G12C, non-G12C) of the tested patients; 68.8 %, 89.3 %, and 87.7 % of the patients received first-line treatment combined with an immune checkpoint-inhibitor in 2019. TPS > 50 % vs. TPS < 1 % was associated with a significantly decreased risk of mortality in a multivariate Cox model (HR 0.39, 95 % CI 0.26−0.60, p =<0.001). There were no differences in clinical outcome between KRAS wildtype, G12C or non-G12C mutations and KRAS mutational status was not prognostic in the model. Conclusion: Here we describe the so far largest prospectively recruited cohort of patients with advanced NSCLC and KRAS mutations, with special focus on the G12C mutation. These data constitute an extremely valuable historical control for upcoming clinical studies that employ KRAS inhibitors.